China and the challenge of economic globalization the impact of WTO membership - Fung, Hung-gay.; Pei, Changhong; Zhang, Kevin H.; Gale Group (Armonk, N.Y. M.E. Sharpe, 2006)
"Evaluates the implications of China's WTO membership on the nation and provides policy guidance for those doing business in China or working with the Chinese economy."--GVRL description.
List of tables and figures -- Introduction -- Part I. Economic performance after China's accession to the world trade organization -- Part II. The WTO and China's economic welfare -- Part III. Financial reforms and capital markets -- Part IV. Industrial and agricultural development -- About the editors and contributors -- Index.
"An East Gate book."
Electronic reproduction.
Keywords: World Trade Organization -- China; Globalization -- China; Electronic books; China -- Commerce; China -- Economic conditions -- 2000-.